2018
DOI: 10.1007/s11356-018-2126-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation, residue analysis, and risk assessment of fipronil and flonicamid in cotton (Gossypium sp.) samples and soil

Abstract: Cotton crop is highly susceptible to attack by sucking pests. Being an important oilseed and feed crop, it is essential to monitor the pesticides and ensure health protection at consumer level. Therefore, a method was validated to estimate fipronil and flonicamid in various cotton samples and risk assessment was performed. Contamination of oil in the extracts from the various oil seeds and cake samples is a major problem as this oil contaminates the column and interferes with the detection of pesticides. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In the previous literature, the half-lives of flonicamid were 4.8 days in green tea shoots, 5 1.5-4.6 days in cabbages, 9 2.8-3.2 days in honeysuckles, 21 4.6-7.0 days in cottons. 23 Therefore, our results demonstrated that a longer dissipation behavior of flonicamid on peach trees than most reported crops, while shorter than the half-lives of flonicamid (7.6-19 days) in apples. 19 The dissipation behavior of dinotefuran in peach flesh isshown in Fig.…”
Section: Dissipation Of Flonicamid and Dinotefuran In Peachsupporting
confidence: 49%
See 2 more Smart Citations
“…In the previous literature, the half-lives of flonicamid were 4.8 days in green tea shoots, 5 1.5-4.6 days in cabbages, 9 2.8-3.2 days in honeysuckles, 21 4.6-7.0 days in cottons. 23 Therefore, our results demonstrated that a longer dissipation behavior of flonicamid on peach trees than most reported crops, while shorter than the half-lives of flonicamid (7.6-19 days) in apples. 19 The dissipation behavior of dinotefuran in peach flesh isshown in Fig.…”
Section: Dissipation Of Flonicamid and Dinotefuran In Peachsupporting
confidence: 49%
“…Additionally, the ME was analyzed by comparing the calibration slope between the matrix matching standard and the solvent standard. 23 The LODs referred to the corresponding amount of three times the matrix blank background response standard deviation. The LOQs were to determine the minimum amount of the analytes that can be quantified by analyzing a series of samples with known concentrations of the analytes with accuracy and precision to meet the requirements.…”
Section: Validation and Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flonicamid ( N -cyanomethyl-4-trifluoromethylnicotinamide, FLO) is a novel systemic insecticide with selective activity that exhibits very good efficacy in pest control [ 1 3 ]. It is widely applied for foliar treatment of cabbages, tea trees, dwarf berry crops, and fruits [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2018; Chawla et al . 2018). Despite of the toxicity and residues of flonicamid were lower than neonicotinoid insecticides, the toxic of flonicamid to natural enemies of pests had been reported.…”
Section: Introductionmentioning
confidence: 99%